Empathy and perceived burden in caregivers of patients with schizophrenia spectrum disorders - Rosaria Di Lorenzo; Anna Girone; Nunzio Panzera; Gianluca Fiore; Margherita Pinelli; Giulia Venturi; Federica Magarini; Paola Ferri (BMC, 2021)
Abstract Background Caregivers of patients load different kinds of burdens, including emotional distress. Aims of this study were to evaluate both burden and empathy of caregivers who assist patients with schizophrenia spectrum disorders. Methods We selected a sample of 60 caregivers (34 women and 26 men), who assisted patients with schizophrenia spectrum disorders treated in our local Community Mental Health Center for a 1-year minimum period. We administered two scales to our sample, Zarit Burden Interview (ZBI) and Balanced Emotional Empathy Scale (BEES), and collected data of caregivers and their assisted patients in a 3-month period. Data were statistically analyzed. Results We reported a mean ZBI score of 49.68 (±15.03 SD) and a mean BEES score of 14.35 (±9.05 SD), indicating the perception of moderate-severe burden and low level of empathy, respectively. The analysis of internal consistency confirmed the good reliability of both ZBI (Cronbach's alpha = 0.90) and BEES (Cronbach's alpha = 0.77). The correlation between the two scales was not statistically significant at Spearman test. At our multiple linear regression, many variables of both caregiver and patient showed a significant correlation with the ZBI score. In particular, not living with the assisted patient and female gender of caregiver potentially decreased the burden, whereas clinical severity of assisted patient and two caregiver conditions, middle school education and spouse relationship with patient, could worsen the burden. We highlighted two positive statistically significant correlations between the total score of BEES and caregiver characteristics: being spouse and not living with assisted patient. Conclusions Our study highlights that the caregiver burden of patients with severe psychiatric disorders is high and is associated with low emotional empathy experienced by caregivers, probably due to a defensive psychological mechanism. The conditions of spouse and cohabitation can concomitantly increase both empathy and burden in caregivers.